2021
DOI: 10.32725/jab.2021.015
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Dialium guineense pulp on aspirin-induced gastric mucosal injury in albino rats

Abstract: The numerous challenges and detrimental effects connected with the treatment of peptic ulcers in the world today calls for alternative attention. Ethnomedicinally, Dialium guineense pulp (DAGP) has numerous pharmacological activities. This study investigated the antiulcer activities of Dialium guineense pulp on gastric mucosa injury induced with aspirin in albino Wistar rats. DAGP extract was orally administered at doses of 250, 500 and 1000 mg/kg bw (mg per kg of the body weight) per day for 3 or 7 days follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…Thus, the increase in the aggressive factors aforementioned following the administration of Aspirin in this study confirmed that ulcerative stage has been established suggesting a good model for ulceration in rats. This finding is similar to those previous studies [26][27][28]. Likewise, the volume of the gastric juice and acidity are inversely proportional to the pH of the juice, this indicates that the low pH observed in this study is a reflection of the increase in gastric acid secretion due to aspirin administration.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the increase in the aggressive factors aforementioned following the administration of Aspirin in this study confirmed that ulcerative stage has been established suggesting a good model for ulceration in rats. This finding is similar to those previous studies [26][27][28]. Likewise, the volume of the gastric juice and acidity are inversely proportional to the pH of the juice, this indicates that the low pH observed in this study is a reflection of the increase in gastric acid secretion due to aspirin administration.…”
Section: Discussionsupporting
confidence: 92%